The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1038/sj.bjp.0702232
|View full text |Cite
|
Sign up to set email alerts
|

Potassium channel activation and relaxation by nicorandil in rat small mesenteric arteries

Abstract: 1 We used whole-cell patch clamp to investigate the currents activated by nicorandil in smooth muscle cells isolated from rat small mesenteric arteries, and studied the relaxant e ect of nicorandil using myography. 2 Nicorandil (300 mM) activated currents with near-linear current-voltage relationships and reversal potentials near to the equilibrium potential for K + . 3 The nicorandil-activated current was blocked by glibenclamide (10 mM), but una ected by iberiotoxin (100 nM) and the guanylyl cyclase inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…In addition, comparative studies show that relaxation responses to nicorandil are inhibited significantly by the K ATP blocker GLM, but not by the other K + -channel blocker. These findings are in agreement with previous reports (43,44).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, comparative studies show that relaxation responses to nicorandil are inhibited significantly by the K ATP blocker GLM, but not by the other K + -channel blocker. These findings are in agreement with previous reports (43,44).…”
Section: Discussionsupporting
confidence: 83%
“…These findings show that FLNT and nicorandil exhibit a dual mechanism of action acting partly as a nitrate and partly as a K + -channel opener. Our findings of two pathways for relaxation by nicorandil are consistent with two previous reports (43,44), while not consistent with other observations using piglet mesenteric arteries pre-contracted by noradrenaline (47). The reasons of the variable contribution of K ATP channel opening and stimulation of sGC on nicorandil-induced relaxation depend on the differences in the animal species, tissues, size of vessels, and agonist studied (48).…”
Section: Discussionsupporting
confidence: 82%
“…30 -32 In rat mesenteric arteries, small-conductance K ATP (K NDP ) channels (Ϸ25 pS, in symmetric high K ϩ ) have been identified that are regulated by nucleoside diphosphates (UDP or GDP) and ATP acting from the inside. 33,34 The molecular identity of the aortic and mesenteric K ATP channels is not absolutely established. Two Kir6.x subunits have been cloned to date: Kir6.1 and Kir6.2 that differ in their single channel conductance.…”
Section: Discussionmentioning
confidence: 99%
“…Nicorandil acts on both sarcolemmal and mito-KATP channels, 40 and also has a nitrate effect. 41 The effect of diazoxide was completely blocked by 5-HD, but its effect on nicorandil was not complete, as shown by Fig 4. This may be attributed to its combined effect, although it was small in the present study.…”
Section: Discussionmentioning
confidence: 99%